The molecular structure of microtubule-associated protein 1A (MAP1A) in vivo and in vitro. An immunoelectron microscopy and quick-freeze, deep- etch study - Shiomura, Y (J Neurosci, 1987)
We studied the distribution of microtubule-associated protein 1A (MAP1A) in Purkinje cell dendrites by means of electronmicroscopic immunocytochemistry, using a monoclonal antibody (McAb) against MAP1A; this was combined with the observation of the 3-dimensional cytoskeletal ultrastructure in dendrites via the quick-freeze, deep- etch technique (QF-DE). We prepared a McAb against rat brain MAP1. This McAb recognized MAP1A on a nitrocellulose filter through use of the immunoblotting method, and stained immunofluorescently Purkinje cell perikarya, dendrites, and axons. Using the McAb, we labeled rat cerebellum extracted with Triton X-100 and simultaneously fixed with aldehyde, followed by gold-labeled rabbit anti-mouse IgG. Gold particles were attached to the filamentous, fuzzy materials, mostly those connected to microtubules (MTs), but were hardly localized on those attached to neurofilaments (NFs). The 3-dimensional cytoskeletal ultrastructure of fresh Purkinje cell dendrites was revealed by QF-DE. In Purkinje cell dendrites, MT was a predominant cytoskeletal element, whereas only a few NFs were found. Fine, elaborate cross-bridges filled up the interstices among MTs, and between MTs and other cellular components. Cross-bridges linking MTs to one another were composed mainly of a fine filamentous structure, frequently branching and anastomosing at several sites, and appeared somewhat granular. We ensured that the cross-bridges observed in saponin-extracted tissues were not a result of artifactual condensations or precipitations of soluble proteins during deep etching. The molecular structure of MAP1A was further investigated by the rotary shadowing technique. The affinity-purified MAP1A was a long, thin, filamentous, and very flexible molecule.(ABSTRACT TRUNCATED AT 250 WORDS)